Analysis of the reasons and costs of hospitalization for epilepsy patients in East China. (November 2019) - Yu, Nian; Lin, Xing-jian; Zhang, Shu-gang; Di, Qing
Highlights: Epilepsy suffered from long inpatient hospital stays with high mortality and costs. The leading causes of hospitalization for epilepsy were stroke & Parkinson disease. The reason for highest hospital fees of epilepsy inpatients was Parkinson disease. Epilepsy with comorbid depression should be monitored to prevent suicide initially. Abstract: Purpose: This study aimed to assess the cause and cause-specific risks of hospitalization for epilepsy patients in East China. Further analysis was performed for inpatient hospitalization days, hospital mortality and costs. Method: This study was performed on epilepsy patients admitted to our hospital including 21 community health centers in East China from January 2011 to April 2017. Case records including patient data, length of hospitalization, reasons for admission, hospital mortality, and the costs incurred for hospitalization of epilepsy patients were reviewed. Results: The three principal reasons for admission were: 1) cerebral vascular disease (CVD), 2) newly diagnosed epilepsy with unknown etiology; and 3) frequent seizures including status epilepticus. The median length of hospitalization was 13 days. The three major reasons regarding inpatient days were: 1) Parkinson's Disease (PD), 2) dementia, 3) trauma. The average hospital mortality was 14.81‰ (17/1148) with 1) lung infection (mainly pneumonia), 2) depression (deaths occurred by suicide) and 3) frequent seizures including status epilepticus being the three top reasons. The three major financial cost incurred for in-patients with epilepsy were: 1) PD, 2) arteriovenous malformation and 3) trauma. Conclusions: The most common hospitalized reasons for epilepsy patients were CVD, PD and dementia, which all were common diseases in the elderly. Consequently, the hospitalization days of these patients were longer and their financial burden was heavier. Epilepsy patients with comorbid depression should be closely monitored to prevent suicide from the onset of epilepsy.